The Relationship between Parental Factors and the Incidence of Stunting Among Toddlers at Balung Community Health Center - Roby Aji Permana Roby Aji Permana; Ida Maghfiroh (Journal of Nursing Periodic, 2026)
Introduction: Stunting is a chronic nutritional problem in toddlers that affects children’s physical growth and cognitive development and can reduce the quality of human resources. The condition is influenced by various factors including parental factors. This study aims to analyze the relationship between parental factors and the degree of stunting in toddlers at the Integrated Management Clinic for Sick Toddlers at the Balung Community Health Center. Methods: This study uses a quantitative, cross-sectional design. The study sample consisted of 44 mothers of infants aged 2 to 59 months with stunting selected purposively. Results: The analysis revealed that most respondents reported household incomes below the regional minimum wage. The majority of parents had completed their education at the junior or senior high school level. An authoritarian approach to parenting was predominantly practiced. In addition, household food diversity was limited, with most households providing fewer than five nutrient groups. Statistical testing showed that parental socioeconomic status was not significantly associated with the degree of stunting. Parents' educational attainment also showed no meaningful association with stunting severity. Conclusions: Statistical analysis demonstrated that parenting patterns, family socioeconomic status, and parental education level were not significantly associated with the degree of stunting among toddlers, as indicated by p-values> 0.05. Household food availability also showed no significant relationship with stunting severity, suggesting that adequate household food availability does not necessarily ensure optimal child growth in this study.